Afterword. Issue 1 (1st March 2011) - Choi, Jinhee
Many essays in this volume attempt to emphasize how the significance of a horror and/cult film does not and should not limit itself to its heuristic, epistemic value; in other words, as a vehicle to "learn" about that culture and nation-state. Rather, with an accumulation of enough scholarship on Asian horror films, the scope and methods can vary, not to pigeonhole films to dominant theoretical frameworks, but to provide nuanced explanations to the relationship between films and their surroundings culture, industry, fandom, and aesthetics. The essays in this volume certainly take us in that direction plurality of interest, topic, and methodology.